Development of integrated zinc oxide nanorods coated glass substrate sensing device / Haziezol Helmi Mohd Yusof - Haziezol Helmi , Mohd Yusof (2020)
A simple and practical cost-effective integrated zinc oxide (ZnO) nanorods coated glass substrate sensing device for humidity and formaldehyde vapor sensing applications is reported. The developed sensor device is composed of a commercial light-emitting diode (LED) and photodiode that correspondingly served as light source and detector which precisely positioned on a 3D printed sensor platform. A receiver circuit and Arduino platform were employed for signal amplification and processing. A uniform ZnO nanorods coating were grown on the surface of glass substrate via hydrothermal method by controlling the growth durations and coating length. A standard reference for the optimum working condition of sensing device was presented by maximizing the dynamic range of the fabricated glass substrates towards humidity sensing. The first order of theoretical model was derived in which two new normalized parameters (Z and ζ) were introduced. An experimental validation was performed and showed well correlation towards the theoretical approach. The optimum sensing response of the sensor device was found to be effective by the determination of parameter Z and ζ instead of a specific growth conditions (growth duration and coating length). The fabricated sensor device was successfully characterized towards humidity and formaldehyde vapor concentrations. A significant response towards relative humidity (RH) levels between 35% and 90% was exhibited which the output voltage reduced in non-linear trend by 750 mV with average sensitivity of -12 mV/%. The sensing performance of the sensor device produced an average response time of 3.8 s for relative humidity (RH) level from 35% to 85% and showed quicker recovery time of 2.2 s. The device also demonstrated good response in detecting formaldehyde vapor concentrations with good sensing stability at small change of concentration as low as 1%.